Generalized abeille tiles: Topologically interlocked space-filling shapes generated based on fabric symmetries. (June 2020) - Akleman, Ergun; Krishnamurthy, Vinayak R.; Fu, Chia-An; Subramanian, Sai Ganesh; Ebert, Matthew; Eng, Matthew; Starrett, Courtney; Panchal, Haard
Highlights: We have introduced the concept of Generalized Abeille Tiles (GATs) that are generalizations of Abeille vaults, introduced by architect Joseph Abeille. We have developed to develop a theoretical framework for GATs that leverages the theory of bi-axial 2-fold woven fabrics. We provide algorithms for constructing GATs by using 2D and 3D Voronoi decomposition with higher dimensional Voronoi sites (curves and surfaces) based on bi-axial woven fabrics. We present a comparative structural analysis of GATs as individual shapes as well as tiled assemblies for three different fabric patterns using plain and twill weave patterns. Graphical abstract: Abstract: In this paper, we present a simple and intuitive approach for designing a new class of space-filling shapes that we call Generalized Abeille Tiles (GATs). GATs are generalizations of Abeille vaults, introduced by the French engineer and architect Joseph Abeille in late 1600s. Our approach is based on two principles. The first principle is the correspondence between structures proposed by Abeille and the symmetries exhibited by woven fabrics. We leverage this correspondence to develop a theoretical framework for GATs beginning with the theory of bi-axial 2-fold woven fabrics. The second principle is the use of Voronoi decomposition with higher dimensional Voronoi sites (curves and surfaces). By configuring these new Voronoi sites based on weave symmetries, we provide a method for constructing GATs. Subsequently, we conduct a comparative structural analysis of GATs as individual shapes as well as tiled assemblies for three different fabric patterns using plain and twill weave patterns. Our analysis reveals interesting relationship between the choice of fabric symmetries and the corresponding distribution of stresses under loads normal to the tiled assemblies.